Trunk kinematics and motor unit behavior during different loads and speeds in individuals with and without aberrant movement patterns during active forward bending: A cross-sectional study - Peemongkon Wattananon; Sasithorn Kongoun; Katayan Klahan; Sheri P. Silfies; John R. Gilliam; Jim Richards (PLoS ONE, 2025)
Background Instability catch (IC) during active forward bending is an aberrant movement pattern observed in patients with low back pain. Increasing load and speed may show different responses in kinematics and motor unit behavior including peak amplitudes (pAMP) and mean firing rates (mFR). Objectives This study aimed to compare kinematic patterns under different loads and speeds and explored the motor unit behavior in individuals with and without IC. Methods 17 participants were classified as having IC and 10 participants were classified as having no IC from clinical observations. Inertial measurement units were used to quantify kinematic parameters, and decomposition electromyography (dEMG) was used to investigate motor unit behavior. Participants performed 2 sets of 1-minute forward bending under low load and low speed (LL), high load and low speed (HL), and low load and high speed (LH) conditions. Results Significant between-group differences (P < 0.05) were found in kinematic parameters. Significant within-group changes (P < 0.05) were found between the LL and HL conditions for all kinematic parameters in individuals with IC. Individuals without IC demonstrated significant within-group changes (P < 0.05) between LL and LH in mFR, while individuals without IC showed changes in both pAMP and mFR. Conclusion These kinematic parameters may represent IC. Changes in motor unit behavior suggest that individuals with and without IC used different strategies to perform this task. Clinicians may consider varying the speed of movement to challenge the trunk neuromuscular control system and design interventions to address motor unit firing rate.